SGCE mutations cause psychiatric disorders: clinical and genetic characterization - Peall, Kathryn J. (2013)
Myoclonus dystonia syndrome is a childhood onset hyperkinetic movement disorder characterized by predominant alcohol responsive upper body myoclonus and dystonia. A proportion of cases are due to mutations in the maternally imprinted SGCE gene. Previous studies have suggested that patients with SGCE mutations may have an increased rate of psychiatric disorders. We established a cohort of patients with myoclonus dystonia syndrome and SGCE mutations to determine the extent to which psychiatric disorders form part of the disease phenotype. In all, 89 patients with clinically suspected myoclonus dystonia syndrome were recruited from the UK and Ireland. SGCE was analysed using direct sequencing and for copy number variants. In those patients where no mutation was found TOR1A (GAG deletion), GCH1, THAP1 and NKX2-1 were also sequenced. SGCE mutation positive cases were systematically assessed using standardized psychiatric interviews and questionnaires and compared with a disability-matched control group of patients with alcohol responsive tremor. Nineteen (21%) probands had a SGCE mutation, five of which were novel. Recruitment of family members increased the affected SGCE mutation positive group to 27 of whom 21 (77%) had psychiatric symptoms. Obsessive–compulsive disorder was eight times more likely (P < 0.001) in mutation positive cases, compulsivity being the predominant feature (P < 0.001). Generalized anxiety disorder (P = 0.003) and alcohol dependence (P = 0.02) were five times more likely in mutation positive cases than tremor controls. SGCE mutations are associated with a specific psychiatric phenotype consisting of compulsivity, anxiety and alcoholism in addition to the characteristic motor phenotype. SGCE mutations are likely to have a pleiotropic effect in causing both motor and specific psychiatric symptoms.